Pemerolehan Bahasa Kedua Dalam Perkembangan Bahasa Pada Anak - Nabilla Annajwa; Muh. Habibulloh (Journal of Arabic Education and Linguistic, 2025)
This study discusses the process of language acquisition in children by highlighting the conceptual differences between language acquisition and language learning according to key figures such as Stephen Krashen, B.F. Skinner, and Noam Chomsky. The purpose of this study is to describe the stages of children's language development and explain how the theories of behaviorism and innateness explain the mechanisms by which children acquire their first and second languages. The study uses a qualitative method with a literature study approach, which collects data from journals, articles, and academic works related to second language acquisition in children. The results show that language acquisition occurs naturally and subconsciously through intensive interaction with the environment, while language learning is formal and conscious in the classroom context. Skinner's theory emphasizes the role of stimulus-response and habituation in the formation of verbal behavior, while Chomsky emphasizes the existence of the Language Acquisition Device (LAD) as an innate device that processes linguistic input into language rules. This study concludes that informal environments rich in verbal interaction, especially within the family, play a dominant role in the success of children's language acquisition, while formal educational environments strengthen aspects of awareness and mastery of language structures.